A dental implant dislocated in the ethmoidal sinus: A case report. Issue 5 (May 2020) - Cascio, Filippo; Basile, Gianpaolo Antonio; Debes Felippu, Alexandre Wady; Debes Felippu, Andrè Wady; Trimarchi, Fabio; Militi, David; Portaro, Simona; Bramanti, Alessia
Abstract: Maxillary sinusitis can represent a rare complication of dental implants of endodontic materials impinging in the maxillary sinuses. The effects of anatomical variants of paranasal sinuses on pathophysiological and clinical manifestations of dental sinusitis are poorly understood. Herein, we present a case of dislocation of a dental implant in the ethmoidal sinus in a 63-years old man with bilateral accessory maxillary orifice. This anatomical variation, by providing an additional way for the drainage of mucus in the maxillary sinus, could have allowed the dislocation of the implant in the ethmoidal sinus without causing mucus stagnation and consequent sinusitis, leading to a unusual clinical presentation. . Abstract : Anatomy; Dental surgery; Dental materials; Eye-ear-nose-throat; Medical imaging; Dentistry; Dental implant; Chronic sinusitis; Atypical sinusitis; Endoscopic sinus surgery.